COMPARATIVE ANALYSIS OF VISION PATHOLOGY IN THE POPULATION OF DONBASS: INFLUENCE OF HEAVY METALS AND CONSEQUENCES OF STRESS-INDUCED STATES - Дмитрий Олегович Ластков; Виктория Викторовна Попович (Medicina v Kuzbasse, 2023)
The aim of research was consisted in assessment of heavy metals’ influence on morbidity and prevalence of eye appendage diseases in population of the ecocrisis region, including in conditions of military and epidemic distress’ consequences. A significant increase of eye diseases in children and adolescents, and decrease in adults has been since the beginning of the local military conflict. The consequences of stress-induced states were aggravated the adverse effect of heavy metals on morbidity of all population groups.